A STUDY ON CORPORATE COMPLICITY PRINCIPLES UNDER INTERNATIONAL CRIMINAL LAW - Pramod, Shinde Hema; Singh, Narendra Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
orporate complicity in international crimes is an emerging area of concern under international criminal law. This study examines the principles and frameworks governing corporate accountability for their involvement in crimes such as genocide, war crimes, and crimes against humanity. It traces the historical evolution of the concept from the Nuremberg Trials, explores key international instruments like the Rome Statute, and analyzes notable cases such as Kiobel v. Royal Dutch Petroleum. The study also highlights the challenges in prosecuting corporate entities, including jurisdictional issues, evidentiary hurdles, and the complexities of the corporate veil. Recent developments, including universal jurisdiction expansions and negotiations for a binding treaty on business and human rights, demonstrate progress in addressing these gaps. The article concludes by recommending strengthened legal frameworks, enhanced due diligence mechanisms, and the establishment of specialized tribunals to ensure justice and accountability.